Apprehensions and Expectations of the Adoption of Systematically Planned, Outcome-Oriented Practice. (July 2013) - Savaya, Riki; Altschuler, Dorit; Melamed, Sharon
Objectives: The study examined social workers' apprehensions and expectations of the impending adoption of systematically planned, empirically based, outcome-oriented practice (SEOP). Method: Employing a mixed methods longitudinal design, the study used concept mapping to identify and map workers' apprehensions and expectations and a self-reported questionnaire to measure their levels. Results: Apprehensions were that SEOP will increase monitoring and financial considerations in decision making and undermine professional intervention and professional responsibility. Expectations were that it will (a) empower social workers to provide better service and better cope with counterpressures and (b) systemize work procedures and improve organizational efficiency, effectiveness, and governance. Findings also showed that workers, who participated in formulating the system's guidelines and principles, reported lower apprehensions and higher expectations than those who did not. Conclusions: In introducing SEOP, it is important to take workers' apprehensions and expectations into consideration and to include workers in the development stage.